Rencana Lansekap Wisata Edutani Di Kebun Percobaan Fakultas Pertanian, Universitas Udayana - SEMARAJAYA, COKORDA GEDE ALIT; LILA, KOMANG ARTHAWA; SUDARSANA, ANAK AGUNG GEDE DALEM; YUSIANA, LURY SEVITA (Jurnal Arsitektur Lansekap, 2017)
Bali is an agrarian island but the interests of Balinese people are very limited to the agricultural sector. Faculty of Agriculture-Udayana University is primarily responsible for improving human resources in agriculture and the development of the agricultural sector in Bali. One of the facilities owned by the faculty is experimental garden. In addition to being a center of education and research, the experimental garden is also expected to introduce the agricultural field through recreational activity to thel public. By developing experimental garden as a tourist destination requires a study to determine a tourist attraction. However, having a tourist attraction will not ensure if it is matched with the experimental garden management as well as the tourism development program. This study aims to plan agricultural landscape educational tourism (Edutani) in faculty experimental garden of Udayana University. The research method was conducted with Gold (1980) planning of recreation activity approach which is consist with some steps i.e. inventory, analysis, synthesis, concept and landscape plan. This research resulted a landscape plan for Faculty of Agriculture experiment garden for edutani tourism development.